Histomorphometric analysis of homogenous demineralized dentin matrix as osteopromotive material in rabbit mandibles - Pinheiro Carvalho, Valéria Abrantes [UNESP]; De Oliveira Tosello, Darcy; De Castillo Salgado, Miguel Angel [UNESP]; Fernandes Gomes, Mônica [UNESP] (My University, 2004)
Purpose: The aim of this work was to evaluate the effectiveness of homogenous demineralized dentin matrix (HDDM) slices in surgical bone defects created in the mandibles of rabbits and occluded with a polytetrafluoroethylene (PTFE) membrane in the promotion of bone growth. Materials and Methods: Surgical bone defects were created in 36 adult rabbits and divided into 4 groups: bone defect (control), bone defect with PTFE membrane, bone defect with HDDM, and bone defect with both HDDM and a PTFE membrane (HDDM + PTFE). The rabbits were sacrificed after 30, 60, and 90 days, and the bone defects were examined histologically and by histomorphometric analysis (analysis of variance and the Tukey test). Results: The volume of newly formed bone matrix was significantly greater in the HDDM and HDDM + PTFE groups than in the control and PTFE groups. The discrete inflammatory reaction found in the HDDM and HDDM + PTFE groups did not prevent the osteopromotive activity of the dentin matrix. Discussion: HDDM slices were biocompatible and were resorbed during the bone remodeling process. They stimulated the newly formed bone until 30 days after implantation. Conclusion: Bone repair was accelerated in the bone defects treated with HDDM in comparison to the control group.
Keywords: Bone repair; Guided tissue regeneration; Homogenous demineralized dentin matrix; Osteopromotion; Tissue engineering; anesthetic agent; antibiotic agent; diclofenac; ketamine; pentabiotic; pentabiotico; politef; rompum; unclassified drug; analysis of variance; animal experiment; animal model; animal tissue; bone demineralization; bone growth; bone matrix; bone remodeling; controlled study; dentin; evaluation; examination; histology; inflammation; jaw malformation; mandible; membrane; morphometrics; nonhuman; osteolysis; rabbit; stimulation; tooth implantation; tooth occlusion; Analysis of Variance; Animals; Biocompatible Materials; Bone Matrix; Bone Remodeling; Bone Substitutes; Dental Materials; Dentin; Guided Tissue Regeneration; Haversian System; Mandibular Diseases; Membranes, Artificial; Osteogenesis; Polytetrafluoroethylene; Rabbits; Time Factors